Development of Attitude Assessment Instruments in Environmental Pollution Practicum Activities - Nadiah Danisha Putri; Sarah Talia; Rizhal Hendi Ristanto; Dini Safitri; Fitria Pusparini (Bioeduca : Journal of Biology Education, 2025)
Assessment in practical activities only focuses on cognitive and psychomotor aspects, while attitude assessment tends to be neglected. This condition indicates the need to develop a valid and reliable attitude assessment instrument to support a more comprehensive assessment. This study aims to develop an attitude assessment instrument based on validated and reliable observation techniques in the context of environmental pollution practical activities. This study uses a type of development research (Research and Development) with a development design that refers to the ADDIE model. The subjects of this study include: (1) Three expert validators who are lecturers of Biology Education, and (2) 36 students of class X.A SMAN 89 Jakarta. Data analysis was carried out through logical validation by experts and empirical validity and reliability tests using Product Moment correlation analysis and Cronbach's Alpha reliability formula. The results of the logical validation carried out by three experts showed that the attitude assessments assessed were all valid, with an average of 78.36%. At the implementation stage, empirical validity and reliability tests were conducted on 36 students and obtained eight valid attitude aspects with calculated r results > r table. Then all valid attitude aspects were tested for reliability and the result was 0.422, so that the instrument developed was included in the fairly reliable category.